PENGARUH RASIO PERPUTARAN TOTAL ASSET, RASIO PERPUTARAN PIUTANG, RASIO PERPUTARAN PERSEDIAAN DAN CURRENT RATIO TERHADAP PROFITABILITAS: PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Reslianty Rachim (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2024)
The purpose of this study was to determine the effect of total asset turnover ratio, accounts receivable turnover ratio, inventory turnover ratio and current ratio on profitability in food and beverage sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The data collection technique uses purposive sampling. The sample is a company listed in the food and beverage sector on the Indonesia Stock Exchange totaling 21 companies with data from 2018-2022. This research analysis uses multiple linear regression analysis with the help of the SPSS Ver 29 computer program. The results showed that the total asset turnover ratio had a positive and significant effect on profitability, the accounts receivable turnover ratio had no effect on profitability, the inventory turnover ratio had a positive and significant effect on profitability and the current ratio had a significant effect on profitability in food and beverage sector companies listed on the Indonesia Stock Exchange 2018-2022 period. Simultaneously there is an effect of total asset turnover ratio, accounts receivable turnover ratio, inventory turnover ratio, and current ratio.